Nursing diagnoses, interventions and outcomes in the bariatric surgery postoperative care - Rosa Aparecida Nogueira Moreira; Lívia Moreira Barros; Andrea Bezerra Rodrigues; Joselany Áfio Caetano (Universidade Federal do Ceará, 2013)
One aimed to identify the nursing diagnoses of the cardiovascular/pulmonary response class belonging to the activity/rest domain, according to the taxonomy II of NANDA-I in patients in the bariatric surgery immediate postoperative period and propose the interventions and nursing outcomes according to the Nursing Interventions Classification and the Nursing Outcomes Classification. This exploratory and cross-sectional study was carried out from July 2010 to June 2011 with 59 patients in the bariatric surgery immediate postoperative period. The most frequent nursing diagnoses were: Ineffective Peripheral Tissue Perfusion; Decreased Cardiac Output; Activity Intolerance; Risk for Decreased Cardiac Tissue Perfusion; and Risk for Ineffective Renal Perfusion. A nursing care plan was constructed with 16 interventions and 10 expected outcomes. The choice of appropriate interventions decreases hospitalization time and consequently the cardiopulmonary complications in the postoperative period. Another important issue is the standardization of language in the construction of the diagnoses and outcomes, which improves nursing documentation.